1999
DOI: 10.1007/bf02496247
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy of liquid crystals based on lanthanide mesogenic complexes

Abstract: The values of magnetic anisotropy of smectic A-phases for a number of lanthatdde complexes (LH)2LM(NO3)2, where M = Nd, Eu, Gd, Tb, Dy, Ho, and Er, and LH is a Schiff's base), were measured. These values are two orders of magnitude larger than those normally found for diamagnetic liquid crystals and are well correlated with magnetic birefringence constants and molecular magnetic anisotropy of nonmesogenic lanthanide diketonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Several authors 14,16,44 used the Bleaney theory, 23 which was developed for predicting the pseudocontact contribution to the proton NMR shift for paramagnetic lanthanide complexes. Depending on the sign of ⌬ , the theory is able to predict whether an upfield of downfield shift of the proton signal can be expected in the presence of a shift agent.…”
Section: B Variation Of the Sign And Magnitude Of ⌬ In The Series Ofmentioning
confidence: 99%
“…Several authors 14,16,44 used the Bleaney theory, 23 which was developed for predicting the pseudocontact contribution to the proton NMR shift for paramagnetic lanthanide complexes. Depending on the sign of ⌬ , the theory is able to predict whether an upfield of downfield shift of the proton signal can be expected in the presence of a shift agent.…”
Section: B Variation Of the Sign And Magnitude Of ⌬ In The Series Ofmentioning
confidence: 99%
“…As an example, the Schiff base met- allomesogens 150 (Fig. 150) [131] are shown; a series of other achievements of this research group in this area is reported in [132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147]. o-Cyclopalladates, such as the cyclopalladated azomethines 151 (Fig.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…151), belong to a special, most researched group of these compounds [127]. The metallomesogenes [127,[132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147] include also the lanthanide complexes of ␤-ketoenamines 152 (Fig. 152) [148][149][150].…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Recently, a number of works devoted to synthesis of transition metal complexes with liquid crystalline properties has appeared [4][5][6]. Such compounds differ from other non-metal mesogens by high electric and magnetic susceptibilities and high anisotropy of their values, luminescent and light absorbance properties [7][8][9]. The most intriguing problems in this field are connected with the description of the specific interactions of metal species with mesogenic molecules and their relation to intermolecular forces determining the liquid crystalline behavior of the system.…”
Section: Introductionmentioning
confidence: 99%